A influência das restrições de sono nas escolhas alimentares: uma revisão sistemática - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Sleep is defined as a complex physiological condition, where changes in physiological and behavioral processes occur. Sleep scarcity is considered a chronic stressor, which is accompanied by anxiety, depression, irritation and apathy. The presence of stress modifies eating behavior, redirecting preferences to foods with greater palatability and high energy value. The aim of this paper was to conduct a systematic review to investigate the influence of sleep restrictions on eating behavior. The articles were identified through PubMed, Lilacs, Cochrane and Scielo databases. For search strategies, the following keywords were used: “sleep”, “food”, “nutrition”. Through the search strategy, a total of 1318 articles were initially identified, and after deleting the duplicates (131), 1187 articles were selected by title and abstract. After applying the exclusion and reading criteria of titles and abstracts, 26 articles were selected to read the full text. Of these, 15 articles were selected for the present study. In view of the results obtained, it is evident that individuals submitted to periods of sleep restrictions have erroneous food selections, prioritizing the consumption of sweet, processed foods and sugary drinks.
Keywords: Alimentos; Sono; Nutrição; Food; Sleep; Nutrition; CNPQ::CIENCIAS DA SAUDE